Analisis Teknik Deep Focus Dalam Menciptakan Komposisi Visual Pada Film “Sang Prawira” - Irham Setiawan; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Film is a mass communication medium that is very popular with the public. Interesting techniques are needed to increase the appeal of a film. One of the deep focus techniques in the film